An experimental study on the mitigation effects of fine water mist on confined-blast loading and dynamic response of steel plates. (December 2019) - Kong, Xiangshao; Zhou, Hu; Zheng, Cheng; Liu, Haibao; Wu, Weiguo; Guan, Zhongwei; Dear, John P.
Highlights: Experiments of confined explosions of different masses of TNT with and without water mist were performed. The mechanism of water mist mitigating confined-blast loading and dynamic responses of steel plates was revealed. The suppressing effect of water mist on combustion of detonation products of TNT was analysed. The mitigation effect of fine water mist on the response of blasted loaded plate was determined quantitatively. Abstract: The blast loading from an explosion of a condensed explosive in a confined space is quite different from that in an open environment. Due to the confinement effect, a confined-blast load usually causes more severe damage. The detonation products from a fuel-rich explosive, such as Trinitrotoluene (TNT), can react with the surrounding air under specific conditions and release additional energy, resulting in a significant increase of reflected shockwaves and quasi-static pressure in a confined space. Mitigation of the confined-blast loading is an effective way to protect structures from destruction. In this paper, a detailed experimental investigation of the influence of water mist on both the mitigation of blast load and dynamic response of the structure is presented. Six cases of experimental tests, with different charge masses of 80, 120 and 160 g of TNT explosive, with and without the presence of water mist, are performed in a confined chamber, with the shock pressure and deflection-time history curves of blast-loaded steel plates being recorded, as well as quasi-static pressure and temperature of the contained gas. By analysing the experimental data, it is found that the water mist decreases the reflected blast wave and quasi-static pressure by restraining the combustion effect and subsequent energy release of detonation products. As a consequence, both the first peak deflection and the residual deformation of the blast-loaded steel plates decrease greatly. Furthermore, based on a non-dimensional analysis of the experimental results for plates with different thickness subjected to different loading conditions, a new empirical relationship between non-dimensional deflection of the plate and a non-dimensional load parameter (for fully confined blast loading) was obtained. By employing this new empirical relation, the mitigation effect of fine water mist on confined blast load was determined quantitatively. The use of water mist is a very good alternative to mitigate the damage of structures subjected to a confined-blast load in the design of anti-blast structures.